2013
DOI: 10.3390/ijms14058899
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Plasma Metabolomic Profiling for Diagnosis of Esophageal Squamous-Cell Carcinoma Using an UPLC/TOF/MS Platform

Abstract: Epidemiological studies indicated that esophageal squamous-cell carcinoma (ESCC) is still one of the most common causes of cancer incidence in the world. Searching for valuable markers including circulating endogenous metabolites associated with the risk of esophageal cancer, is extremely important A comparative metabolomics study was performed by using ultraperformance liquid chromatography-electrospray ionization-accurate mass time-of-flight mass spectrometry to analyze 53 pairs of plasma samples from ESCC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…A previous metabolomics study of EAC serum specimens using a case-control design also included cases with Barrett’s esophagus 7, 8 . However, that study did not include an external validation and the sample sizes were small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous metabolomics study of EAC serum specimens using a case-control design also included cases with Barrett’s esophagus 7, 8 . However, that study did not include an external validation and the sample sizes were small.…”
Section: Discussionmentioning
confidence: 99%
“…To date, metabolomic studies on EC included profiling serum and urine samples to identify differential metabolite markers between patients and controls 5,6 and potentially useful metabolic profiles for diagnosis of either SCC 7 and EAC 8 . However, no external validation was included and no insight into biochemical processes altered in EC was provided.…”
Section: Introductionmentioning
confidence: 99%
“…PS, PA, PC, PI, PE and sphinganine 1-phosphate were overexpressed in cancer patient plasma compared to healthy controls. This demonstrated the critical role of PLs in the SCC oncogenesis; therefore, the identification of novel biomarkers could be an important strategy to reaching an early diagnosis that could improve clinical outcome [106]. Biomarkers’ diagnostic value has been recently evaluated by Uchiyama and colleagues, with the intention of distinguishing biomolecule distributions through IMS, in 11 signals between neoplasm and stromal regions.…”
Section: Lipidomics In Cancer Researchmentioning
confidence: 99%
“…Metabolomics, the global semi-quantitative assessment of endogenous small molecule metabolites within a biological system, has been successfully utilized in cancer biomarker discovery (Spratlin et al 2009;Zhang et al 2013, b;Ke et al 2015). Up to now, a few ESCC metabolomics studies has been reported using specimen of serum (Djukovic et al 2010;Zhang et al 2011;Ikeda et al 2012;Zhang et al 2012aZhang et al , b, 2013Jin et al 2014;Mir et al 2015), plasma (Hasim et al 2012;Liu et al 2013;Xu et al 2013;Ma et al 2014), urine (Davis et al 2012;Hasim et al 2012), tissue (Wu et al 2009;Yakoub et al 2010;Wang et al 2013;Yang et al 2013;Lynam-Lennon et al 2014) or gastric content (Kumar et al 2012), and conducted on mass spectrometry (MS) and nuclear magnetic resonance (NMR) platforms. These studies revealed significantly perturbed metabolic expression in ESCC patients compared with healthy controls.…”
Section: Introductionmentioning
confidence: 95%